1957
DOI: 10.1172/jci103510
|View full text |Cite
|
Sign up to set email alerts
|

Response of Pulmonary Artery Pressure and Total Pulmonary Resistance of Untrained, Convalescent Man to Prolonged Mild Steady State Exercise1

Abstract: Although many published studies relevant to the effects of exercise on the gross pulmonary hemodynamics of patients with heart disease are available in the literature, few data are to be found which deal with normal man (1-6). There have been conflicting claims that there is no increase, no significant increase, a consistent increase, or an occasional decrease in the pulmonary artery pressure of normal man as the result of exercise loads eventuating in oxygen uptakes up to 400 ml. per M.2 per min. (2) and pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1966
1966
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The decline of pressure in our studies appears to follow a time course similar to that reported for MPAP by Sancetta and Rakita during prolonged steady state exercise (57). The decrease of MPAP observed by Widimsky, Berglund, and Malmberg during repeated exercise seems also to have a time constant of the same order (58).…”
Section: Pulmonary Vascular Distensibilitysupporting
confidence: 88%
“…The decline of pressure in our studies appears to follow a time course similar to that reported for MPAP by Sancetta and Rakita during prolonged steady state exercise (57). The decrease of MPAP observed by Widimsky, Berglund, and Malmberg during repeated exercise seems also to have a time constant of the same order (58).…”
Section: Pulmonary Vascular Distensibilitysupporting
confidence: 88%
“…1) [8][9][10][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. After the exclusion of individuals with prospectively defined implausible data, 222 subjects (147 males, 33 females, 42 sex not available) were analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the exercise protocol is important since pressures and flow resistance in the lesser circulation tend to fall after a few minutes of exercise [12,24], or when exercise periods are repeated [25]. Thus the rise in pulmonary artery pressure may not be as much as expected with progressive increments in work load, when exercise periods are prolonged or repeated exercise is used.…”
Section: Discussionmentioning
confidence: 99%